Acute disseminated encephalomyelitis associated with SARS-CoV-2 in a 21-month-old: a case report - Cecília Gomes-Pereira; Beatriz Sousa; Sara Nogueira-Machado; Valentina Ribeiro; Catarina Magalhães (Publicaciones Permanyer, 2024)
Introduction: Since its emergence in 2019, SARS-CoV-2 has been responsible for a myriad of symptoms affecting multiple organ systems, including the central nervous system. Although rare, especially in children, cases of acute disseminated encephalomyelitis (ADEM) associated with COVID-19 have also been described. Case report: We present the case of a previously healthy 21-month-old girl who presented with altered consciousness and ataxia ten days after SARS-CoV-2 infection was reported. Cranioencephalic MRI revealed hyperintense T2-weighted and hypointense T1-weighted lesions. The remaining imaging, analytical, autoimmune, and serological studies showed no alterations, allowing a diagnosis to be established. Therapy with pulses of prednisolone was initiated with excellent results. Discussion: This case report highlights the importance of a high index of suspicion in a child presenting with encephalopathy days to weeks after SARS-CoV-2 infection. A quick diagnosis is vital for early treatment and to improve the clinical course and long-term outcome.